Hyperleptinemia is associated with parameters of low-grade systemic inflammation and metabolic dysfunction in obese human beings - Leon-Cabrera, Sonia; Solís-Lozano, Lourdes; Suárez-Álvarez, Karina; González-Chávez, Antonio; Béjar, Yadira L.; Robles-Díaz, Guillermo; Escobedo, Galileo (Frontiers in Integrative Neuroscience, 2013)
Leptin is an adipose tissue-derived hormone that has been involved in hypothalamic and systemic inflammation, altered food-intake patterns, and metabolic dysfunction in obese mice. However, it remains unclear whether leptin has a relationship with parameters of systemic inflammation and metabolic dysfunction in humans. We thus evaluated in a cross-sectional study the circulating levels of leptin in 40 non-obese and 41 obese Mexican individuals, examining their relationship with tumor necrosis factor alpha (TNF-a), interleukin (IL) 12, IL-10, central obesity, serum glucose and insulin levels, and serum triglyceride and cholesterol concentrations. Circulating levels of leptin, TNF-a, IL-12, IL-10, and insulin were measured by ELISA, while concentrations of glucose, triglyceride, and cholesterol were determined by enzymatic assays. As expected, serum levels of leptin exhibited a significant elevation in obese individuals as compared to non-obese subjects, showing a clear association with increased body mass index (r=0.4173), central obesity (r=0.4678), and body fat percentage (r=0.3583). Furthermore, leptin also showed a strong relationship with serum TNF-a (r=0.6989), IL-12 (r=0.3093), and IL-10 (r=-0.5691). Interestingly, leptin was also significantly related with high concentrations of fasting glucose (r=0.5227) and insulin (r=0.2229), as well as elevated levels of insulin resistance (r=0.3611) and circulating triglyceride (r=0.4135). These results suggest that hyperleptinemia is strongly associated with the occurrence of low-grade systemic inflammation and metabolic alteration in obese subjects. Further clinical research is still needed to determine whether hyperleptinemia may be a potential marker for recognizing the advent of obesity-related metabolic disorders in human beings.